2010
DOI: 10.1097/olq.0b013e3181e50026
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2a Study Assessing Colonization Efficiency, Safety, and Acceptability of Lactobacillus crispatus CTV-05 in Women With Bacterial Vaginosis

Abstract: LACTIN-V colonized well, and was safe and acceptable in women treated for BV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 23 publications
2
96
0
2
Order By: Relevance
“…25 The study which was conducted at San Francisco General Hospital (SFGH) recruited 24 pre-menopausal women with BV from clinics in the San Francisco Bay Area and randomized them 3:1 to receive either LACTIV-V or placebo. L. crispatus CTV-05 culture and 9-bacterium specific 16S rRNA gene quantitative PCR assays were then done on vaginal swabs collected on several study visits from the 18 women receiving LACTIN-V.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 The study which was conducted at San Francisco General Hospital (SFGH) recruited 24 pre-menopausal women with BV from clinics in the San Francisco Bay Area and randomized them 3:1 to receive either LACTIV-V or placebo. L. crispatus CTV-05 culture and 9-bacterium specific 16S rRNA gene quantitative PCR assays were then done on vaginal swabs collected on several study visits from the 18 women receiving LACTIN-V.…”
Section: Methodsmentioning
confidence: 99%
“…22;23 A higher concentration of L. crispatus CTV-05 (2 × 10 9 cfu/dose) administered as a powder using a prefilled tampon-like applicator in healthy women as well as women with BV was also found to be safe and acceptable. 24;25 In a phase 2A trial, 61% of women were successfully colonized with L. crispatus CTV-05 at either day 10 or day 28 and 44% colonized at day 28. 25 Factors causing a sub-optimal vaginal colonization with exogenous lactobacilli are unknown, but could include high levels of BV-associated bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaginal colonization with humanderived L. crispatus strain CTV-05 has been successful [24]. Lactobacillus crispatus CTV-05 was used as a vaginal suppository for healthy women with a history of recurrent urinary tract infections (UTIs) [25,26] and for the treatment of BV [27]. It should be mentioned that healthpromoting effects of probiotics are usually strain specific.…”
Section: Introductionmentioning
confidence: 99%
“…However, as discussed above, it could be suggested that the treatment effect was not due to clindamycin alone considering the contribution of intensive co-treatment with estrogenic patches. Another upcoming adjuvant to or maybe even stand-alone treatment of AVM, is live biotherapeutic products (LBPs) or probiotics (Ross et al, 2008; Hemmerling et al, 2010; Larsson et al, 2011). However, strain documentation and manufacturing issues call upon well-conducted RCTs with strain specific LBPs to adequately assess the treatment effect of these new drugs.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%